2018
DOI: 10.1088/1361-6528/aae8c1
|View full text |Cite
|
Sign up to set email alerts
|

Few-layer bismuthene for femtosecond soliton molecules generation in Er-doped fiber laser

Abstract: Bismuthene, a mono-elemental two-dimensional material with a novel kind of few-layer structure purely consisting of bismuth, has been predicted to have a prominent optical response and enhanced stability in theory. In this paper, few-layer bismuthene is employed as the saturable absorber. The mode-locker is fabricated by dropping bismuthene on a microfiber in a passively mode-locked, Er-doped fiber laser. The single pulse can be obtained at 122.1 mW, with 621.5 fs pulse duration at 1557.5 nm central wavelength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 39 publications
(42 reference statements)
0
59
0
Order By: Relevance
“…Recent studies found that MXene, antimonene, bismuthene, and metal‐organic framework (MOF) have also excellent saturable absorption property and can be used in mode‐locked/Q‐switched lasers. For example, the researchers achieved the soliton mode‐locked fiber laser based on MXene, antimonene, and Ni‐MOF, respectively.…”
Section: Versatile Pulsed Lasers Using 2d Layered Materialsmentioning
confidence: 99%
“…Recent studies found that MXene, antimonene, bismuthene, and metal‐organic framework (MOF) have also excellent saturable absorption property and can be used in mode‐locked/Q‐switched lasers. For example, the researchers achieved the soliton mode‐locked fiber laser based on MXene, antimonene, and Ni‐MOF, respectively.…”
Section: Versatile Pulsed Lasers Using 2d Layered Materialsmentioning
confidence: 99%
“…In addition to having excellent mechanical properties, bismuthene is a narrow bandgap semiconductor and is stable at high temperatures . Few layer bismuthene has been used as SAs in mode‐locked fiber lasers, producing stable fs pulses ≈1550 nm . Among other group V elements, antimonene has also been used as an SA in passive Q‐switched lasers and shown stable ns pulse widths for laser emission at 946, 1064, and 1342 nm .…”
Section: Photonic and Optoelectronic Applicationsmentioning
confidence: 99%
“…However, the existing 2DM-based SAs also have their own shortcomings. In order to overcome the existing shortcomings of 2DMs and achieve wide applications in industry, some other mono-elemental 2D materials, such as antimonene and bismuthene, have attracted more attention [225][226][227][228][229][230][231][232][233]. In 2017, Song et al experimentally investigated the broadband non-linear optical response of few-layer antimonene as SA, and obtained ~550-fs pulses in an Erdoped fiber laser [225].…”
Section: Perspectivementioning
confidence: 99%